Managing with Agility (Journal of Universal Excellence, 2026)
Research Question (RQ): What does the agility in the work environment present and which actors are of particular importance in achieving agility?Purpose: With this article, they would like to point out that we do not have to talk about the kind of medical management, but also about agile methods, such as the above-mentioned traditional management, which allow it more adaptability and flexibility.Method: Review of technical and scientific literature.Results: Agile management methods are a response to the problem of marshikers, which classifies classical management. People with agile misery believe that their talents and learning skills can be developed and promoted scientifically. People with agile misery are bound to non-formal learning and are endowed with people who help them to progress and become more painful.Organization: It is important that companies, in turn, find the most appropriate medium between agile and standard management approaches. Against changing the environment of the project, agile management is in any case more appropriate.Society: It is very important that the projects are implemented effectively. Projects must be successful, with the lowest costs and high levels of quality, and in line with the project's objectives. In short, projects must provide certain benefits that the company has identified as important and, in addition, that the company has decided to carry out the project.Originality: Effective management of the change is closely linked to the solution of problems on the launcher when introducing the change in the working environment. They shall always be combined with the human factor, which may be applied in an appropriate manner to the relevant approach.Limitations/Future Research: Further research would be impressively extended to a specific organization.
Keywords: project; management; agility; company; changes; working environment